2006
DOI: 10.1007/s10126-005-0113-9
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the Gastrointestinal Tract of the Farmed South African Abalone Haliotis midae by the Probionts Vibrio midae SY9, Cryptococcus sp. SS1, and Debaryomyces hansenii AY1

Abstract: Viable cell counts and/or in situ hybridization were used to determine whether the probionts Vibrio midae SY9, Cryptococcus sp. SS1, and Debaryomyces hansenii AY1 can colonize the gastrointestinal tract of the South African abalone Haliotis midae. The number of culturable probiotic cells reisolated from H. midae fed probiotic-supplemented feed for 3 weeks ranged from 10(6) to 10(7) cfu/g gut material. A significant decrease (P < 0.05) in probiont numbers 2 days after feeding the probiotic-supplemented feed had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…As a result, they enhance VSCFA production and digestive enzyme activities in the gut of H. gigantea. Previous studies have demonstrated the ability of putative probiotic microorganisms to colonize [5,11,13,27,28] or show probiotic effects [4,8,[29][30][31][32] in the gut of fish and shellfish, but this is the first study of LAB probiotic colonization and activity in the gut of an abalone species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they enhance VSCFA production and digestive enzyme activities in the gut of H. gigantea. Previous studies have demonstrated the ability of putative probiotic microorganisms to colonize [5,11,13,27,28] or show probiotic effects [4,8,[29][30][31][32] in the gut of fish and shellfish, but this is the first study of LAB probiotic colonization and activity in the gut of an abalone species.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are thought to confer health benefits by stimulation of host immune responses and improvements in nutrition [1]. Most probiotics tested for use in aquaculture have been preparations of Gram-negative bacteria such as Vibrio [4,5] and Pseudomonas [6]; Gram-positive bacteria such as Bacillus [7] and lactic acid bacteria (LAB); yeasts such as Saccharomyces [8] and Debaryomyces [4]; and microalgae such as Tetraselmis [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When testing the persistence of probiotics in the digestive tract of the fish, the Bps3 strain maintained a higher cell count up to the tenth week after suspending the foodcontaining probiotics. The permanence of the probiotics in the faeces evidenced the great colonizing power of the digestive tract of the fish in contrast with other aquatic organisms, such as the Abalone mollusc, which show a marked decrease in probiotic cells during the first and second days after ceasing probiotic feed and show low amounts of these cells (p<0.05) in their faeces 15 days later (Macey & Coyne, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…These higher counts indicate that the Bsp2 strain was better to colonize the digestive tract of the fish (p< 0.05) and will thrive as long as this probiotic is provided. Studies performed with aquatic organisms have also shown that, when supplying different strains of probiotics, even if they all colonise, there will always be one strain that dominates or varies its number of cells over time (Gildberg et al, 1997;Ringo and Vadstein, 1998;Ringo & Olsen., 1999;Rengpipat et al, 2000;Nikoskelainen et al, 2003;Gullian et al, 2004;Macey & Coyne, 2006;). When testing the persistence of probiotics in the digestive tract of the fish, the Bps3 strain maintained a higher cell count up to the tenth week after suspending the foodcontaining probiotics.…”
Section: Discussionmentioning
confidence: 99%